When Zoo became Nature - Gjerløff, Anne Katrine (Tidsskrift for kulturforskning, 2010)
This article points out central historical themes in the debates and arguments given by the directors of Copenhagen Zoo for the zoo as an alternative to nature. When Copenhagen Zoo was founded in 1859, its purpose was divided equally between entertainment, enlightenment and symbolizing the glory of the Danish capital. During this period though, it also became possible for the zoo to stage itself as a kinder place for animals than "real" nature. In the early 20th century, the zoo attracted attention from animal rights movements, wherefore the debates came to be structured around two radically different perceptions of nature. The article takes its outset in the arguments formulated by the three successive directors: Julius Schiøtt, Waldemar Dreyer and Theodor Alving.